The Relationship Between Growth Mindset and Academic Achievement Among Secondary School Students: The Mediating Role of Academic Self-Efficacy - Tang, Miaomiao; Wang, Jingxian; Zeng, Zhen (Journal of Research in Vocational Education, 2025)
Research on the relationship between middle school students’ growth mindset and academic self-efficacy was carried out by using the Academic Procrastination Questionnaire and the Academic self-efficacy Scale as research tools, and a survey was conducted among 634 junior high school students who were randomly selected in clusters. The results showed that: (1) Middle school students’ growth mindset and academic self-efficacy were above the medium level; (2) The score of academic self-efficacy was higher than that of academic ability self-efficacy; (3) There was a significant positive correlation between middle school students’ growth mindset and academic self-efficacy; (4) Academic self-efficacy played a partial mediating role between the growth mindset pattern and students’ academic performance.